Clinical and Histopathological Findings in a Patient of Darier–White Disease with Acrokertasosis Verruciformis of Hopf - Vikash Paudel; Manish Bhakta Pradhan; Brijesh Shrestha; Sumit Paudel (Case Reports in Dermatological Medicine)
Darier disease (DD) is a rare genodermatoses characterized by greasy hyperkeratotic papules in seborrheic regions and nail and oral changes. Histologically, it presents as suprabasal clefts with acantholytic and dyskeratotic cells. Acrokertasosis verruciformis of Hopf (AKVH) is considered an allelic variant with clinical overlap where Church spires are seen histologically without dyskeratoses. Patients are susceptible to various viral and bacterial skin infections requiring prevention and treatment of infection. Nonspecific treatment includes patient counseling on exacerbating factors. Although there are no curative treatments for DD, topical corticosteroids and systemic retinoids may be used to control inflammation and hyperkeratosis. We are reporting a rare case with clinical and histological findings of DD with AKVH in a 17-year-old boy with keratotic papules, presented on the hands and feet, nose, and ears without mucosal involvement.